A Feasibility Study of Solar Collector for Preheating Feed Water of Wood-Fired Boiler System - ชุมนุมวัฒน์, ศุภชัย; หลีชัย, นิติกร; เครือผือ, ธงชัย (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The purpose of this research was to determine feasibility of investing in the use of solar collectors to preheat feed water of a wood-fired boiler, in order to reduce fuel cost for the canned fruit factory at Phanatnikhom district, Chonburi province. Two types of solar collectors studied were evacuated tube and flat plate solar collector, both with compound parabolic concentrator. The feasibility of investment was determined by analysis of thermal efficiency, as well as cost and economic value of solar collector. Results of this research revealed that an average thermal efficiency of the evacuated tube and the flat plate solar collectors with compound parabolic concentrator were 60.6 % and 58.1 %, with a difference of 1.8 oC in feed water temperature between the two types of solar collector. Considering the feasibility of investment from both thermal efficiency and cost of solar collector, it was found that the cost of evacuated tube solar collector with compound parabolic concentrator was higher than that of flat plate solar collector at 4,365 baht per square meter. However, both types could produce feed water at the similar temperature level. Consequently, the flat plate solar collector with compound parabolic concentrator seemed to be a promising alternative to invest for preheating feed water of wood-fired boiler system. It could reduce the boiler’s fuel cost by 45,639.70 baht per year with solar collection area of 119.07 m2. The NPV of this project was 10,887.80 baht, with the IRR of 0.32 % and the payback period of 14.83 years.